Multidisciplinary team meetings in treatment of spinal muscular atrophy adult patients: a real-life observatory for innovative treatments - Emmanuelle Salort-Campana; Guilhem Solé; Armelle Magot; Céline Tard; Jean-Baptiste Noury; Anthony Behin; Elisa De La Cruz; François Boyer; Claire Lefeuvre; Marion Masingue; Louise Debergé; Armelle Finet; et al. (Orphanet Journal of Rare Diseases, 2024)
Abstract Background In 2017, a new treatment by nusinersen, an antisense oligonucleotide delivered by repeated intrathecal injections, became available for patients with spinal muscular atrophy (SMA), whereas clinical trials had mainly involved children. Since 2020, the oral, selective SMN2-splicing modifier risdiplam has been available with restrictions evolving with time. In this peculiar context of lack of data regarding adult patients, many questions were raised to define the indications of treatment and the appropriate follow-up in this population. To homogenize access to treatment in France, a national multidisciplinary team meeting dedicated to adult SMA patients, named SMA multidisciplinary team meeting, (SMDTs) was created in 2018. Our objective was to analyze the value of SMDTs in the decision-making process in SMA adult patients and to provide guidelines about treatment. Methods From October 2020 to September 2021, data extracted from the SMDT reports were collected. The primary outcome was the percentage of cases in which recommendations on validating treatment plans were given. The secondary outcomes were type of treatment requested, description of expectations regarding treatment and description of recommendations or follow-up and discontinuation. Data were analyzed using descriptive statistics. Comparisons between the type of treatment requested were performed using Mann–Whitney test or the Student t test for quantitative data and the Fisher’s exact test or the χ2 test for qualitative data. Results Cases of 107 patients were discussed at the SMDTs with a mean age of 35.3 (16–62). Forty-seven were SMA type 2, and 57 SMA type 3. Twelve cases were presented twice. Out of 122 presentations to the SMDTs, most of requests related to the initiation of a treatment (nusinersen (n = 46), risdiplam (n = 54), treatment without mentioning preferred choice (n = 5)) or a switch of treatment (n = 12). Risdiplam requests concerned significantly older patients (p = 0.002), mostly SMA type 2 (p < 0.0001), with greater disease severity in terms of motor and respiratory function compared to requests for nusinersen. In the year prior to presentation to the SMDTs, most of the patients experienced worsening of motor weakness assessed by functional tests as MFM32 or other meaningful scales for the most severe patients. Only 12% of the patients discussed had a stable condition. Only 49/122 patients (40.1%) expressed clear expectations regarding treatment. The treatment requested was approved by the SMDTs in 72 patients (67.2%). The most common reasons to decline treatment were lack of objective data on the disease course prior discussion to the SMDTs or inappropriate patient’s expectations. Treatment requests were more likely to be validated by the SMDTs if sufficient pre-therapeutic functional assessment had been performed to assess the natural history (55% vs. 32%) and if the patient had worsening rather than stable motor function (p = 0.029). In patients with approved treatment, a-priori criteria to define a further ineffectiveness of treatment (usually after 14 months of treatment) were proposed for 67/72 patients. Conclusions In the context of costly treatments with few controlled studies in adults with SMA, in whom assessment of efficacy can be complex, SMDTs are ‘real-world observatories’ of great interest to establish national recommendations about indications of treatment and follow-up.